2009
DOI: 10.1080/00365520802588117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecularly defined hypolactasia, self-perceived milk intolerance and milk consumption on bone mineral density in a population sample in Northern Europe

Abstract: Self-perceived milk-intolerance rather than HL influences milk consumption and has deleterious effects on bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Such a self-prescribed reduction is in agreement with a study in Finnish children with the -13910C/C genotype, who naturally diminished their usage of milk [31] and also with a study in children of other ethnicities [42]. It was also shown that other age groups also tend to reduce their milk consumption because of the appearance of symptoms after milk [24,38]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such a self-prescribed reduction is in agreement with a study in Finnish children with the -13910C/C genotype, who naturally diminished their usage of milk [31] and also with a study in children of other ethnicities [42]. It was also shown that other age groups also tend to reduce their milk consumption because of the appearance of symptoms after milk [24,38]. …”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have shown that subjects with intolerance to lactose tend to reduce their consumption of milk, which is predictable as far as they suffer from symptoms after milk consumption [31,35-38]. In our previous study [7] subjects showed no differences between genotypes in the frequency of GI complaints during life.…”
Section: Introductionmentioning
confidence: 68%
“…147 The prevalence of specific malabsorption syndromes (such as lactose, fructose intolerance) is well-established in many countries, 148 but in health surveys many more individuals claim to be lactose intolerant. 149 A similar puzzle seems to be arising with the claims of noncoeliac gluten sensitivity. 150 In a study of >300 patients with a negative hydrogen breath test following lactose challenge, nearly 10% reported abdominal symptoms during the test, and when they were deceptively given glucose before another breath test, half of them reproduced their symptoms, as did 25% of those with lactose malabsorption.…”
Section: Food Intolerancesmentioning
confidence: 93%
“…Additionally, we found a relatively high percentage of patients with genetic determination for lactose intolerance (37%) as compared with the Central European average (20%-40%) [27]. Patients' tending to avoid intolerance symptoms by reducing calcium-rich dairy products might have had a greater impact than the intolerance [5,18,20,25]. Low calcium intake would correlate with an increase in serum parathyroid hormone and increased bone turnover [35].…”
Section: Discussionmentioning
confidence: 99%